2019
DOI: 10.1016/j.wnsx.2018.100005
|View full text |Cite
|
Sign up to set email alerts
|

Clipping on Crossed Wrapping Method for Ruptured Blood Blister-Like Aneurysm of the Internal Carotid Artery: Technical Note and Long-Term Results

Abstract: Background We have been performing the clipping on crossed wrapping (COCW) method using 2 strips of cotton on patients with an internal carotid artery blood blister-like aneurysm (IC-BLA). This method is reliable in preventing the clips from slipping off and the aneurysm walls from being damaged during clipping, and it enables more appropriate and safer clipping. Here we report the technical details of this method and the long-term outcomes of patients receiving this procedure. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Both treatments for BBAs are still greatly challenging for neurosurgeons and neuroradiologists due to the special features of BBAs. Currently, the main treatment options for BBAs include surgical clipping, artery suturing, wrapping and clipping, stent-assisted coiling embolization, multi-stent implantation, and flow-diverting stents ( 2 , 6 , 14 17 ). However, a rescue or second treatment was required in 21% patients, and the overall morbidity and mortality rates were 17 and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatments for BBAs are still greatly challenging for neurosurgeons and neuroradiologists due to the special features of BBAs. Currently, the main treatment options for BBAs include surgical clipping, artery suturing, wrapping and clipping, stent-assisted coiling embolization, multi-stent implantation, and flow-diverting stents ( 2 , 6 , 14 17 ). However, a rescue or second treatment was required in 21% patients, and the overall morbidity and mortality rates were 17 and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the incidences of additional hemorrhage and enlargement after craniotomy are approximately 30% and 4%, respectively, and those after endovascular treatment are approximately 11% and 34%, respectively. [2][3][4][5][6]10) A previous study reported the clippingon-crossed-wrapping method for BBA of the internal carotid artery 11) This method requires circumferential exfoliation, but it is difficult to operate on the deep area of the basilar artery; safe exfoliation at the aneurysmal periphery, which is fragile, is highly difficult. Postoperative recurrence/rebleeding has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the lack of collagen and internal elastic membranes and because of the need to administer antiplatelet and anticoagulant therapy, the perioperative rebleeding rate was higher than in other types of aneurysms, irrespective of the method performed. Even in experienced centers, intraoperative rupture rates in BBAs have been reported to be up to 50% compared with the rate of 7% seen with saccular aneurysms (7). Compared with WCSs, double stent-assisted coils have the possibility of puncturing the aneurysm during the treatment procedure.…”
Section: Rebleedingmentioning
confidence: 99%
“…Compared with endovascular methods, microsurgery can provide a higher occlusion rate. However, the disadvantages of microsurgery include the higher rate of complications and neurologic impairments (6)(7)(8). Technological improvements in intervention devices have led to improved safety and recovery rates associated with endovascular methods (5).…”
Section: Introductionmentioning
confidence: 99%